2008
DOI: 10.1017/s1743923x08000019
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Conditional Support for Torture in the War on Terror

Abstract: The events of September 11 have clearly changed the way that Americans think about politics and policy and may have changed attitudes about the treatment of America's perceived enemies. At the same time, revelations about American interrogation techniques in the war on terror have forced a national dialogue on human rights during a time of war. Americans do tend to oppose a variety of harsh interrogation techniques, but opposition appears to be conditioned by gender, partisanship, and the context in which an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Again, this holds true, he argues, even when Americans are led to believe that a terrorist attack might be imminent and that valuable information could be obtained. Haider-Markel and Vieux (2008) also found that US women are more likely than men to oppose torture, but that the context in which torture is framed matters too – support increases among both groups when they are exposed to messages that suggest that torture could potentially prevent a future attack. Others, however, have shown that public support for torture significantly increases when it is described as a ‘longstanding practice’ (Crandall et al, 2009) or when it is seen as ‘just deserts’ (Liberman, 2014) – retribution for previous terrorist attacks (see also Carlsmith and Sood, 2009).…”
Section: Public Opinion Framing and Question Wordingmentioning
confidence: 97%
See 1 more Smart Citation
“…Again, this holds true, he argues, even when Americans are led to believe that a terrorist attack might be imminent and that valuable information could be obtained. Haider-Markel and Vieux (2008) also found that US women are more likely than men to oppose torture, but that the context in which torture is framed matters too – support increases among both groups when they are exposed to messages that suggest that torture could potentially prevent a future attack. Others, however, have shown that public support for torture significantly increases when it is described as a ‘longstanding practice’ (Crandall et al, 2009) or when it is seen as ‘just deserts’ (Liberman, 2014) – retribution for previous terrorist attacks (see also Carlsmith and Sood, 2009).…”
Section: Public Opinion Framing and Question Wordingmentioning
confidence: 97%
“…In their analysis of survey data from 2001–2009, for example, Gronke et al (2010) noted that the American public remained opposed to torture even when explicit references to terrorism were made in the survey question. Haider-Markel and Vieux (2008), however, using a 2004 national survey, found that public support for torture increased when the policy was framed in the context of terrorism.…”
Section: Public Polling and The Cia Interrogation Programmentioning
confidence: 99%
“…They are the omnipresent features of the digital mediascape, which varies between countries and generations (Curran, Coen, Soroka, Aalberg, Hayashi, Hichy Iyengar, Jones, Mazzoleni, Papathanassopoulos and Rhee, 2014). Furthermore, and in line with the previous studies in this area (Cohrs et al, 2005;Crowson 2009;Haider-Markel and Vieux, 2008), this paper will also take account of the role of some important socio-demographic and personality factors already found relevant (Huddy et al, 2005;McFarland, 2005), including: age, gender, social dominance, and right-wing authoritarianism. As the literature covered here is quite sparse and mostly based on American participants, the paper will contribute to the area by examining the generalisability of the hypothetical grounds to British participants.…”
Section: Digital Securitysupportmentioning
confidence: 59%
“…Women, in particular, may be fi nding the masculinist logic of protection less appealing than they did just a few years ago (Feldman 2004 , Haieder-Markel andVieux 2008). Women, in particular, may be fi nding the masculinist logic of protection less appealing than they did just a few years ago (Feldman 2004 , Haieder-Markel andVieux 2008).…”
Section: The War On Terrormentioning
confidence: 99%
“…Yet as the war drags on, and President Bush’s popularity ratings plunge, we may be seeing the limit of public support for the War on Terror. Women, in particular, may be finding the masculinist logic of protection less appealing than they did just a few years ago (Feldman 2004, Haieder-Markel and Vieux 2008). It is too soon to tell whether the domestic containment ideology associated with the War on Terror will have a lasting presence in American political culture.…”
Section: The War On Terrormentioning
confidence: 99%